Design, Development and Performance Test of Two-Axis Solar Tracker System - Muhammad Ikram, Mohd Rashid; Nik Fadhil, Nik Mohammed; Suliana, Ab Ghani (2014)
Abstract. The energy extracted from photovoltaic (PV) or solar thermal depends on solar insolation. For the extraction of maximum energy from the sun, the plane of the solar collector should always be normal to the incident radiation. Sun trackers move the solar collector to follow the sun trajectories and keep the orientation of the solar collector at an optimal tilt angle. Energy efficiency of solar PV or solar thermal can be substantially improved using solar tracking system. In this paper, an automatic solar tracking system has been designed and developed using DC motor on a mechanical structure with gear arrangement. The movements of two-axis solar trackers for the elevation and azimuth angles are programmed according to the mathematical calculation by using the Borland C++ Builder. Performance of the proposed system over the important parameter like solar radiation received on the collector, maximum hourly electrical power has been evaluated and compared with those for fixed tilt angle solar collector.